Comparación de perfiles de disolución de paracetamol en tabletas de 500 mg multifuente e innovador comercializadas en el Perú - Paredes Ayala, Amarilis Silvia Iris (2014)
Comparison of dissolution profiles of acetaminophen tablets containing 500 mg developed by Natural laboratories and generic (multisource) and Glaxo Smith Klane (innovative) was performed in the present investigation. In the dissolution test 12 tablets of each formulation means were used: pH1.2 acid, ethyl phosphate pH4.5 and 6.8; using apparatus II (paddle), 50 rpm, 37 ° C temperature of the +/- 0.5ºC, volume 900 mL medium and dissolution time where each half was up to 60, 30 and 25 minutes respectively. Filtered aliquots of 10 mL of fresh media were taken, diluted, and then read in a UV spectrophotometer at 243 nm. The concentrations were determined from standard curves prepared previously. Temporary percentages of dissolved drug were analyzed by the methods of independent and dependent model. The best fitting model for the three dissolution media was first order, finding that there is a significant difference in the dissolution constant K (0.274, 0.313) in the media of pH 4.5 and 6.8. Only the mean dissolution time (MDT) where the highest value was in the middle pH 4.5 (TMD = 5,168) and percent dissolution efficiency (DE%) was to characterize the drug release profile determined where the most value at one time was 20 minutes in pH 6.8 medium (80.4% and innovator multisource 81.9%). Finally, the similarity factor (f2) of the dissolution curves multisource innovative product whose values were greater than 50 were analyzed Therefore, it is concluded that the dissolution profiles of paracetamol tablets are similar to the innovative product multisource Panadol® 500 mg